DEVELOPMENT OF SMALL BUSINESSES BASED ON DIVERSIFICATION - Feruza Rustambek qizi, Rustambekova (PT. Antis International Publisher, 2025)
Objective: This study investigates the strategic role of diversification in enhancing the development and sustainability of small businesses, specifically in Uzbekistan's transitional economy. Method: A mixed-methods approach was employed, combining a literature review, statistical analysis, interviews with 15 small business owners, and a comparative evaluation of diversified versus non-diversified businesses. Secondary data from government and international sources were also analyzed. Results: The research found that small businesses engaging in diversification experienced significant improvements in financial and operational metrics: a 70% increase in income, 75% growth in customer base, and a 140% rise in employment. Novelty: This study contributes new insights into the impact of diversification on small businesses in transitional economies, offering practical recommendations for policymakers to foster innovation, competitiveness, and long-term growth by supporting diversified small enterprises.